A COMPARISON OF PROXIMATE COMPOSITION AND MICROBIAL ASPECT OF BRINED AND UNBRINED MACKEREL (Scomber scrombus) SMOKED USING LIQUID AND OAK SAWDUST SMOKE - Fronthea Swastawati; G.A. Garthwaite; Paul Beers (JOURNAL OF COASTAL DEVELOPMENT, 2000)
Introduction : Smoking of fish has changed its function nowadays from just the preservative task to flavoring and coloring. The method of smoking has also been developed from traditional, which had used a simple technology to the modern method. In recent years, preparation of liquid smoke manufactured from certain varieties of wood pyrolysates have been successfully used as a substitute for the traditional smoking in a kiln. Material and methods : The objective of this study was to compare the effect of cold smoking of mackerel fish on the proximate composition, water activity, salt content and microbial aspect of smoked fish treated using oak sawdust and liquid smoke either salted or un-salted. Sensory analysis was carried out by using score sheet organoleptic and hedonic test. Identification of pathogenic bacteria was done by API-20 E method. Factorial design was administered to compare the effect of traditional and liquid smoke method to brined and unbrined smoked fish. Results and Discussion : The content of protein, lipid, water activity and salt of the two products were not significantly different (p>0.05). This means that the quality between two products were similar. Only moisture content of the products were very significantly different (p>0.01) caused by the phenomenon of osmosis between moisture of fish and brine. Study of liquid smoke treatment was found that liquid smoke was easier compared to oak sawdust smoke. It was also found that smoking reduces the number of colonies of bacteria. The number of colonies were about 1x103/g – 5x103/g after 2 day storage for unbrined smoked fish, while in brined smoked fish, no colonies were found after 3 day storage. Pseudomonas sp were present in both raw mackerel and the unbrined smoked fish sample, but were absent in the brined smoked fish.